Prevalence of Anxiety in Pregnancy during COVID 19 pandemic in Shree Birendra Hospital, Chhauni - Khadka, Shailaja; Khatri, Ratna; Malla, Rosy; Thapa, Sumana; Chand, Arju; Acharya, Indira; Neupane, Bibhusan; Bidari, Sumit; Rai, Kopila; Giri, Kanti Prabha; Bata, Lokendra (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aim: To determine the prevalence of anxiety in pregnancy during COVID19 pandemic in Shree Birendra Hospital, Chhauni Method: It is a cross sectional study conducted at Shree Birendra Hospital Chhauni from July to October 2020 following the ethical approval from IRC. All the pregnant women from first to last trimester attending outdoor visit were included; they were asked to fill up Beck Anxiety Index form. The level of anxiety was compared with demographic data like age, race, parity, and period of gestation, education and occupation. Data were analyzed by using SPSS 20 software. Results: A total of 385 presumably uninfected pregnant women were surveyed in 20-40 (28.45±3.95) years age group from 4 to 41 (27.15±9.4) weeks of pregnancy and 55.6% were multipara. Low-grade anxiety was found 99.5% (BAI= 3.06±3.66). Conclusions: Low-grade anxiety was found in almost all pregnant women during covid pandemic and there was no significant difference by demographic variables.